REPORTING AND INTERPRETING THE COST OF STATE GOVERNMENT. - Freeman, Roger A. (The Accounting Review, 1955)
Over-all comparisons of the size of state expenditures need to be supplemented with a description of the relative share of financial responsibility borne by state and local governments in each state. Cost accounting should provide a variety of unit data, like, how much it costs to educate a child, to maintain a patient in a hospital, to build a mile of concrete road, to process a tax return, to patrol 100 miles of highway, etc. Those unit data have of course, only limited value for interstate comparisons until quality standards and uniform methods of cost accounting are set up. Most states depend for their major improvement programs on the investment market. It would be in the states' interest to make available to investors the kind of information which they are used to getting from other applicants for funds. The National Association of State Budget Officers recognizes the need for comparative figures on public revenues and expenditures. The pioneering work in this field by the Bureau of the Census represents a step in the right direction.